Pengaruh Assurance Dalam Kualitas Pelayanan Kesehatan Terhadap Kepuasan Pasien di Rumah Sakit: Meta-analisis dan Systematic Review Tahun 2015-2025 - Mayarestya, Nita Putriasti; Meilantika, Ayu Diana; Rizky, Ayu (Yayasan Jompa Research and Development, 2025)
Abstract The quality of health services is one of the indicators to assess the success and satisfaction of patients related to the service system while determining the loyalty and image of health institutions. The purpose of this study is to analyze the influence of the assurance dimension in the quality of health services on the satisfaction of inpatients and outpatients in hospitals. This study is a meta-analysis and systematic review study using the PRISMA diagram. Article searches used databases from Google Scholar published in 2015-2025. Article search keywords include